FFT Analysis of a Series Loaded Resonant Converter-Based Power Supply for Pulsed Power Applications. (24th April 2008) - Jadeja, R. B.; Kanitkar, S. A.; Shyam, Anurag
Abstract : An impulse power supply has been designed, simulated, and tested in order to feed the primary of a high-frequency transformer. Pulse power system has been widely used for plasma applications. The operational principle of the pulse power system is that the energy from the input source is stored in the capacitor bank device through a dc-dc converter. Then, when a discharging signal is given, the stored energy is released to the load. The new family of ZCS converters is suitable for high-power applications using insulated gate bipolar transistors (IGBTs). The power converter can achieve zero switching with the aid of high-frequency transformer. The device is capable of charging a 0.1 μ F capacitor up to 5 kV which accounts for a charging power of 5 kJ/s. The novel control algorithm is achieved which eminently considers the nonlinear control characteristics of impulse power supply. The required charging voltage, together with the constraint on the charging time, translates into a required maximum power of 10 kW reduced in this initial version to 5 kW. The difficulty to reliably control such a power at the high-voltage side practically forbids any approach featuring a more or less stabilized DC high-voltage to be generated from a conventional 50 Hz transformer through rectification.